A sexually-transmitted case of ameboma without recent travel: Contribution of Entamoeba histolytica genotyping. Issue 45 (January 2022) - Ouafdi, Asmaa; Collarino, Rocco; Normand, Anne-Cécile; Huguenin, Antoine; Touafek, Fériel; Lazure, Thierry; Boullenois, Hortense; Thellier, Marc; Jauréguiberry, Stéphane
Highlights: Amoebic infection (colitis, extra-intestinal abscesses) due to Entamoeba histolytica ( Eh ) is usually transmitted by the fecal-oral route. It can also be transmitted sexually, particularly among men who have sex with men (MSM) when they are asymptomatic carriers. Genotypic analysis allowed us to understand the sequence of events in this case of sexually-transmitted ameboma without recent travel.